Aging as a target for the prevention and treatment of Alzheimer’s disease - Yap, Lauren E.; Hunt, James E.; Turner, Raymond Scott (Frontiers in Neurology, 2024)
Alzheimer’s disease (AD), the most common etiology of dementia in older adults, is projected to double in prevalence over the next few decades. Current treatments for AD manage symptoms or slow progressive decline, but are accompanied by significant inconvenience, risk, and cost. Thus, a better understanding of the risk factors and pathophysiology of AD is needed to develop novel prevention and treatment strategies. Aging is the most important risk factor for AD. Elucidating molecular mechanisms of aging may suggest novel therapeutic targets. While aging is inevitable, it may be accelerated by caloric excess and slowed by caloric restriction (CR) or intermittent fasting. As such, CR may slow aging and reduce the risk of all diseases of aging, including dementia due to AD. The literature on CR, intermittent fasting, and treatment with polyphenols such as resveratrol—a pharmacologic CR-mimetic—supports this hypothesis based on clinical outcomes as well as biomarkers of aging and AD. More studies exploring the role of CR in regulating aging and AD progression in man are needed to fill gaps in our understanding and develop safer and more effective strategies for the prevention and treatment of AD.